2010
DOI: 10.3102/0162373710367681
|View full text |Cite
|
Sign up to set email alerts
|

Are Students of Color More Likely to Graduate From College if They Attend More Selective Institutions?

Abstract: The study takes advantage of the nontraditional selection process of the Gates Millennium Scholars (GMS) program to test the association between selectivity of 4-year institution attended as well as other noncognitive variables on the college completion rates of a sample of students of color. The results of logistic regression and propensity score matching suggest these students are slightly more likely to graduate from college if they attend a highly selective institution. There is also evidence that other no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This phenomenon is a critical policy issue with significant implications for long-term patterns of inequality in American society. Previous research shows that minority students perform better when they attend the most selective institutions to which they qualify (Bowen et al, 2009;Melguizo, 2010;Roderick et al, 2009) and that racial stratification by institutional selectivity is a durable feature of contemporary America (Massey et al, 2002). In light of these findings, our results should motivate institutional leaders and state and federal policymakers to think creatively about policies and practices that increase minority student enrollments while simultaneously improving retention and graduation rates.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is a critical policy issue with significant implications for long-term patterns of inequality in American society. Previous research shows that minority students perform better when they attend the most selective institutions to which they qualify (Bowen et al, 2009;Melguizo, 2010;Roderick et al, 2009) and that racial stratification by institutional selectivity is a durable feature of contemporary America (Massey et al, 2002). In light of these findings, our results should motivate institutional leaders and state and federal policymakers to think creatively about policies and practices that increase minority student enrollments while simultaneously improving retention and graduation rates.…”
Section: Discussionmentioning
confidence: 99%
“…With an analysis of data from these two sources from 2005 to 2006, the NLSF group was able to collect concrete graduation data for 99% of the students who participated and for Hispanic students, 86% of whom graduated in 6 years. These high graduation rates are expected considering the high academic level of students entering select U.S. institutions (Melguizo, 2010).…”
Section: Instrumentation For the Nlsf Data Setmentioning
confidence: 99%
“…The report by the Institute for Higher Education Policy (IHEP; Ramsey, 2010) summarized data from various studies and provides a larger context for the Gates Millennium Scholars (GMS) program. It appeared that the data that were relevant for our purposes were the same data from a study done by Melguizo (2010), an article already implemented into this review. Therefore, the IHEP report was removed to limit redundancy and dependency but we recommend this report for readers interested in more information regarding GMS.…”
Section: Article Selectionmentioning
confidence: 99%
“…Degree completion. Melguizo (2010) analyzed the effects that GMS had on the degree completion of its recipients. The study found that 92% of GMS recipients received their bachelor's degree after at least 6 years of school.…”
Section: Gms Programmentioning
confidence: 99%
See 1 more Smart Citation